CG8005 Mediates Transit-Amplifying Spermatogonial Divisions via Oxidative Stress in Drosophila Testes - Chen, Wanyin (Oxid Med Cell Longev, 2020)
The generation of reactive oxygen species (ROS) widely occurs in metabolic reactions and affects stem cell activity by participating in stem cell self-renewal. However, the mechanisms of transit-amplifying (TA) spermatogonial divisions mediated by oxidative stress are not fully understood. Through genetic manipulation of Drosophila testes, we demonstrated that CG8005 regulated TA spermatogonial divisions and redox homeostasis. Using in vitro approaches, we showed that the knockdown of CG8005 increased ROS levels in S2 cells; the induced ROS generation was inhibited by NAC and exacerbated by H(2)O(2) pretreatments. Furthermore, the silencing of CG8005 increased the mRNA expression of oxidation-promoting factors Keap1, GstD1, and Mal-A6 and decreased the mRNA expression of antioxidant factors cnc, Gclm, maf-S, ND-42, and ND-75. We further investigated the functions of the antioxidant factor cnc, a key factor in the Keap1-cnc signaling pathway, and showed that cnc mimicked the phenotype of CG8005 in both Drosophila testes and S2 cells. Our results indicated that CG8005, together with cnc, controlled TA spermatogonial divisions by regulating oxidative stress in Drosophila.